Naming Their World in a Culturally Responsive Space: Experiences of Hmong Adolescents in an After-School Theatre Program. (January 2017) - Ngo, Bic
This article draws on ethnographic research of a youth theatre program within a Hmong arts organization to explore the ways in which a culturally responsive program nurtured critical consciousness among Hmong immigrant youth. Hmong youth "named" struggles with stereotypes and acculturation expectations, and constructed positive ethnic identities as Hmong Americans in the theatre program. The study contributes to the after-school youth development scholarship by explicating the ways arts programs within co-ethnic, community-based organizations may afford immigrant youth with a means to rescript life stories, confront injustices perpetrated against them, and feel a sense of agency.